1996
DOI: 10.1117/12.229226
|View full text |Cite
|
Sign up to set email alerts
|

<title>Novel white-light interferometer using an electronically scanned Mach-Zehnder interferometer</title>

Abstract: A theoretical analysis and experimental evaluation of a novel Mach-Zehnder interferometer (MZI), used as a recovery interferometer in an electronically-scanned white-light interferometer is reported. This modified version of a MZI has the advantages of being very simple and compact, with high stability and does not introduce any spatial "misoverlapping" of the beams. In addition, since only one beamsplitter is employed in the interferometer (instead of the usual two used in a conventional MZI), the system is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In spatial fringe formation, the scanning of the OPD of the processing interferometer is achieved by the use of a charge-coupled-device (CCD) array in order to detect the spatial interference fringes formed in the so-called “electronically-scanned” arrangement [7]. Reference [7, 3] used a Michelson interferometer with one of its two mirrors being slightly tilted to form the spatially distributed interference fringes.…”
Section: Previous Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In spatial fringe formation, the scanning of the OPD of the processing interferometer is achieved by the use of a charge-coupled-device (CCD) array in order to detect the spatial interference fringes formed in the so-called “electronically-scanned” arrangement [7]. Reference [7, 3] used a Michelson interferometer with one of its two mirrors being slightly tilted to form the spatially distributed interference fringes.…”
Section: Previous Workmentioning
confidence: 99%
“…Reference [7, 3] used a Michelson interferometer with one of its two mirrors being slightly tilted to form the spatially distributed interference fringes. Computer simulations of reference [3] showed that the misidentification rate of central fringe was almost “zero” and the resolution of 1/400 fringe was obtained at 26 [dB] SNR.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations